Genome assembly, annotation, and comparative analysis of the cattail Typha latifolia. Issue 2 (22nd November 2021) - Widanagama, Shane D; Freeland, Joanna R; Xu, Xinwei; Shafer, Aaron B A
Abstract: Cattails ( Typha species) comprise a genus of emergent wetland plants with a global distribution. Typha latifolia and Typha angustifolia are two of the most widespread species, and in areas of sympatry can interbreed to produce the hybrid Typha × glauca . In some regions, the relatively high fitness of Typha × glauca allows it to outcompete and displace both parent species, while simultaneously reducing plant and invertebrate biodiversity, and modifying nutrient and water cycling. We generated a high-quality whole-genome assembly of T. latifolia using PacBio long-read and high coverage Illumina sequences that will facilitate evolutionary and ecological studies in this hybrid zone. Genome size was 287 Mb and consisted of 1158 scaffolds, with an N50 of 8.71 Mb; 43.84% of the genome were identified as repetitive elements. The assembly has a BUSCO score of 96.03%, and 27, 432 genes and 2700 RNA sequences were putatively identified. Comparative analysis detected over 9000 shared orthologs with related taxa and phylogenomic analysis supporting T. latifolia as a divergent lineage within Poales. This high-quality scaffold-level reference genome will provide a useful resource for future population genomic analyses and improve our understanding of Typha hybrid dynamics.